Artavia Murillo vs. Costa Rica case: Critical analysis and regional possible effects - Silva Abbott, Max (Derecho Público Iberoamericano, 2015)
This paper approaches, regarding the decision of the Inter-American Court of Human Rights in the Artavia Murillo et al vs Costa Rica case, 2012, certain subjects that the International Law of Human Rights is presenting, at the national and international level, due to the evolution it has experienced, from within the Court itself, as well as some of the possible consequences that the region could face in connection with the ruling.